2006
DOI: 10.1063/1.2193046
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in electrical properties and thermal stability of low-temperature-processed Hf–Al–O gate dielectrics

Abstract: In this letter, we report on the low temperature (∼350°C) growth of Hf–Al–O dielectric films with improved thermal stability and electrical characteristics for gate dielectric applications. A higher capacitance and improved interfacial properties were observed in the films deposited with NH3 ambient followed by ultraviolet radiation assisted oxidation annealing. The films containing 10.6at.% Al were found to remain amorphous after a 900°C furnace anneal for 1min in flowing nitrogen. The flat-band voltage was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Elements forming CRN, MCRN, or RCP all show potential to stabilize the amorphous phase of high- k dielectric thin films; thus, the choice of incorporating elements involves an optimization/compromise between a stronger amorphizer and a higher dielectric constant. The film crystallization temperatures at a particular alloying element incorporation level are reported, ,,, but it is sometimes difficult to compare these temperatures because different film thicknesses are employed.…”
Section: Introductionmentioning
confidence: 99%
“…Elements forming CRN, MCRN, or RCP all show potential to stabilize the amorphous phase of high- k dielectric thin films; thus, the choice of incorporating elements involves an optimization/compromise between a stronger amorphizer and a higher dielectric constant. The film crystallization temperatures at a particular alloying element incorporation level are reported, ,,, but it is sometimes difficult to compare these temperatures because different film thicknesses are employed.…”
Section: Introductionmentioning
confidence: 99%
“…These two peaks of Ba 3d 5/2 commonly reported in the literature at lower and higher binding energies, denoted as α and β phases, respectively . The peak at lower binding energy resulted due to Ba atoms in the perovskite phase, whereas the peak at higher binding energydue to nonperovskite environment such as carbonates, oxides, and oxygen vacancies. From the Ba 3d 5/2 spectra, it is evident that the intensity of the perovskite phase gradually increases with increasing sintering temperature, and the intensity reversal of the perovskite and nonperovskite phase is observed at 1350 °C. Such a gradual increase in the intensity of the perovskite phase is due to change in the Ba environment, which is a consequence of structural phase transformation with sintering temperature.…”
Section: Resultsmentioning
confidence: 92%
“…It has been previously shown that by alloying HfO 2 with Al 2 O 3 or other oxides the crystallization temperature could be increased, the structure being able to withstand much higher temperature processes without the degradation of the dielectric properties [3][4][5][6][7]. Most of such studies were performed by depositing samples containing various fractions of HfO 2 and Al 2 O 3 oxides that were submitted to different thermal anneals and then their crystallinity was assessed [7][8][9][10]. Most of such studies were performed by depositing samples containing various fractions of HfO 2 and Al 2 O 3 oxides that were submitted to different thermal anneals and then their crystallinity was assessed [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%